Combined coagulation and membrane microfiltration for removal of natural organic material (nom) - Hillis, Peter (Cranfield University, 1999)
The removal of natural organic matter (NOM) is a key requirement of many processes in potable water treatment. Conventionally, removal of NOM and colloidal material has been achieved by coagulation with inorganic coagulants followed by either direct rapid gravity filtration alone or clarification (sedimentation or flotation) followed by at least one stage of rapid gravity filtration. An alternative to conventional processes is to combine membrane microfiltration (MF) with coagulation for NOM removal. The advantages of MF technology over traditional sand filters is the maintenance of an absolute barrier throughout the filtration process, thereby enhancing the physical separation process by presenting an absolute barrier to suspended materials. This thesis presents the results from such a system. A 9.6m2 hollow fibre hydrophilic polysulphone MF membrane system was used in combination with ferric sulphate under controlled pH conditions. The system was operated under constant flow condition and the coagulant concentration varied to assess performance. Coagulation conditions which promoted rapid aggregation of particles was found to give best performance with respect to pressure development, this coincided with a zeta potential at or near zero. Also, a pre-flocculation time of 20 seconds was found to be sufficient to allow complete removal of material associated with the coagulation process. Comparison with other workers showed similar results for the specific cake resistance despite considerable differences in both the scale and type of system used.